Development, Characterization and Pharmacokinetic Profile of Chitosan-Sodium Tripolyphosphate Nanoparticles Based Drug Delivery Systems for Curcumin - Wawaimuli Arozal; Melva Louisa; Deni Rahmat; Priska Chendrana; Ni Made Dwi Sandhiutami (Tabriz University of Medical Sciences, 2021)
Purpose: This study aimed to provide the method of preparation, characterization of curcumin-loaded chitosan-sodium tripolyphosphate (NaTPP) nanoparticle, and evaluate its pharmacokinetic profiles. Methods: Curcumin-loaded chitosan-NaTPP nanoparticles were synthesized using ionic gelation methods. Curcumin was dissolved using surfactants and cosurfactants. Chitosan polymer was then mixed in the curcumin solution and dripped with NaTPP solution until nanoparticle formation. The mucoadhesive study was evaluated by measuring the fluorescence of curcumin within the prepared nanoparticles. The pharmacokinetic profiles of curcumin particles and nanoparticles were then assessed in rats by administering a single oral dose of 100 mg/kg BW. Blood samples were taken from nine predetermined time points, and curcumin plasma concentrations were then analyzed using UPLC-MS/MS. Results: The particle size of the curcumin nanoparticles obtained were 11.5 nm. Entrapment efficiency (EE) of curcumin nanoparticles were exceeding 99.97%, and drug loading capacity (DLC) was 11.34%. The mucoadhesive properties of the nanoparticles were superior to that of curcumin particles. Pharmacokinetic evaluation in rats revealed that curcumin nanoparticles resulted in an increase of area under the curve (AUC), maximum concentration (Cmax), earlier time to reach maximum concentration (Tmax), and lower clearance (CL). Conclusion: Curcumin-loaded chitosan-NaTPP nanoparticles is an effective formulation to improve curcumin plasma concentrations. Thus, enable its applications for the treatment of various diseases.